The value of liver scanning in pediatric age group with special emphasis on histopathological correlation - Erbengi, Günaydın (The Turkish Journal of Pediatrics, 1975)
Liver scintigraphy is one of the most practical and appropriate diagnostic tests in shedding light to the liver disorders.A liver scintigraphy is imperative to differentiate space-occupying lesions, from non-space-occupying lesions of the liver and neighbouring organs.It is very useful for follow-up studies of the cases who had had operations and chemotherapy.